A single- and multiple-dose study to investigate the pharmacokinetics and pharmacodynamics of opicapone, a novel COMT inhibitor, in rat. (October 2017) - Gonçalves, Daniela; Alves, Gilberto; Fortuna, Ana; Bonifácio, Maria João; Soares-da-Silva, Patrício; Falcão, Amílcar
Abstract: Opicapone is a novel catechol- O -methyltransferase (COMT) inhibitor that emerged to fulfil the need of a safer and more efficacious COMT inhibitor. The present study was carried out in order to assess and compare the pharmacokinetics and pharmacodynamics (COMT inhibition) of opicapone after single and multiple oral administrations (30 mg/kg) to Wistar rats. For this purpose, at predefined time points up to 72 h post-dosing, blood, liver and kidneys were collected and, then, the concentrations of opicapone and its active metabolite (BIA 9–1079) were determined in plasma and in liver and kidney tissues, as well as the erythrocyte, liver and kidney COMT activity. No systemic, renal or hepatic accumulation of opicapone was observed following repeated administration. Furthermore, the tissue-systemic exposure relationships to opicapone suggested a low drug exposure in the liver and kidneys. After single-dosing, COMT inhibition profiles were reasonably comparable in all the studied matrices; although similar results were found after multiple-dosing, a higher degree of inhibition was observed, indicating a continuous peripheral COMT inhibition when opicapone is administered once-daily. Despite having a short elimination half-life (≤2.94 h), opicapone showed a strong and long-lasting COMT inhibition in both studies, since more than 50% of the COMT activity was still inhibited at 24 h post-dosing. Graphical abstract: Highlights: Opicapone was rapidly absorbed and eliminated after oral administration to rats. No systemic, renal or hepatic accumulation of opicapone occurred after multiple-doses. A low exposure of the liver and kidney to opicapone was observed. A strong, sustained and long-lasting COMT inhibition was shown in all matrices.